Potential of Bacillus sp., Pseudomonas fluorescens, and Trichoderma sp. Consortium as an Alternative Soybean Growth Medium Against Ralstonia solanacearum in Vitro - Ahmad Davin Najwan Adhyasta; Tri Mujoko; Arika Purnawati (Universitas Labuhanbatu, 2025)
Background: Ralstonia solanacearum is a bacterium highly adaptive to tropical and subtropical environments and can survive for long periods in the soil. This pathogen has a wide host range and is capable of causing severe damage to tomato plants, even leading to total crop failure until 100%. Therefore, appropriate control of these pathogens using biological agents is necessary. Soybean media is considered suitable for propagating Bacillus sp., Pseudomonas fluorescens, and Trichoderma sp. due to its adequate nutritional content and economic value. Previous studies have addressed microbes or media separately, such as PDA or NA, whereas this study combines microbial consortia and alternative media in a single integrated test. This study aims to examine the compatibility and antagonistic ability of a consortium of Bacillus sp., P. fluorescens, and Trichoderma sp. cultured on a soybean-based alternative medium against the bacterium Ralstonia solanacearum under in vitro conditions. Methodology: Observations were made on microbial compatibility and inhibition ability against R. solanacearum using thee double layer pepper disk diffusion methode. Findings: The compatibility test results showed that the microbial consortium was compatible and grew optimally on the soybean-based alternative medium. The highest compatibility index (CI) was observed in the Bacillus sp. + P. fluorescens treatment (0.402), while the lowest CI was found in the Trichoderma sp. × Bacillus sp. + P. fluorescens combination (0.873). In the antagonism test, the combination of Trichoderma sp. + Bacillus sp. × P. fluorescens produced an average inhibition zone of 17.2 mm, categorized as strong. Meanwhile, the Bacillus sp. + P. fluorescens treatment had the lowest average inhibition zone of 9.3 mm, categorized as moderate. Contribution: This study indicate that the consortium of Bacillus sp., P. fluorescens, and Trichoderma sp. maintains compatibility and antagonistic activity against R. solanacearum when grown on alternative soybean-based media, which has generally been tested on conventional media. This study recommends the utilization of soybean-based media as an alternative for developing microbial consortia of antagonists in the control of bacterial wilt disease